2008
DOI: 10.1186/1756-9966-27-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment and outcome of pulmonary hamartoma: a retrospective study of 20-year experience

Abstract: Background: Controversy still exists in the indication and timing of surgical treatment of pulmonary hamartoma (PH). The objective of this study is to summarize the experience and the outcome of the surgical treatment for pulmonary hamartomas, and to assess the effectiveness and necessity of surgical therapy administered in patients with pulmonary hamatoma as well as clinical and pathological features and long-term follow-up results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 27 publications
3
68
0
14
Order By: Relevance
“…These tumors are predominantly composed of cartilage. Other components include fibromyxoid connective tissue, fat, bone, and smooth muscle (1)(2)(3)(4)(5). Most tumors of the tracheabronchial tree are malignant.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These tumors are predominantly composed of cartilage. Other components include fibromyxoid connective tissue, fat, bone, and smooth muscle (1)(2)(3)(4)(5). Most tumors of the tracheabronchial tree are malignant.…”
Section: Resultsmentioning
confidence: 99%
“…They are distributed throughout both lungs. While Guo et al (1) reported that in terms of the location of the lesions, there was no significant difference between the right and the left lung, Fudge et al (6) found that the lesions were located in the right lung in 20 of the 29 patients. Two previous studies were reported that all lobes were affected, with a preponderance in the upper lobes (5, 6).…”
Section: Casementioning
confidence: 96%
See 3 more Smart Citations